Comparison of the efficacy of second and third generation lentiviral vector transduced CAR CD19 T cells for use in the treatment of acute lymphoblastic leukemia both in vitro and in vivo models - Sawaisorn, Piamsiri; Atjanasuppat, Korakot; Uaesoontrachoon, Kitipong; Rattananon, Parin; Treesuppharat, Worapapar; Hongeng, Suradej; Anurathapan, Usanarat (PLOS ONE, 2023)
T cells genetically engineered to express a chimeric antigen receptor (CAR) specifically binding to a CD19 antigen has become the frontline of hematological malignancies immunotherapy. Their remarkable antitumor effect has exerted complete remission in treating B-cell malignancies. Although successful patient treatment has been shown, improvement to the structure of CAR to enhance its safety and efficacy profile is warranted. Transduction with a lentiviral vector (LVV) leading to the expression of CARs is also a critical step in redirecting T cells to target specific tumor antigens. To improve the efficacy of CD19 CARs in this study, the transduction ability of second and third generations LVV were compared. Ex vivo expansion of CD19 CARs T cells from healthy donors’ peripheral blood mononuclear cells was performed after transduction of T cells with second and third generations LVV. Transduction efficacy of transduced T cells was determined to show a higher percentage in the third generations LVV transduced cells, with no changes in viability and identity of cells characterized by immunophenotyping. Testing the cytotoxic capacity of third generations LVV-transduced T cells against target cells showed higher reactivity against control cells. Cytokine expression was detected on the CD19 CARs T cells, suggesting that these cells limit in vitro growth of B-cell leukemia via secretion of the pro-inflammatory cytokine IFN γ. To investigate whether the third generation LVV transduced T cells can limit CD19 lymphoma growth in vivo, an analysis of tumor burden in a mouse model assessed by bioluminescence imaging was performed. We found that, in the presence of CD19 CARs T cells, the level of tumor burden was markedly reduced. In addition, an increase in the length of survival in mice receiving CAR-CD19 T cells was also observed. This suggests that transduction with third generations LVV generate a functional CAR-CD19 T cells, which may provide a safer and effective therapy for B-cell malignancies.